2019
DOI: 10.1111/jonm.12789
|View full text |Cite
|
Sign up to set email alerts
|

The courage to speak out: A study describing nurses' attitudes to report unsafe practices in patient care

Abstract: Aim:To identify workplace factors that influence patient advocacy among registered nurses (RNs) and their willingness to report unsafe practices.Background: A prior study by Black illustrated that 34% of respondents were aware of conditions that may have caused patient harm but had not reported the issue. The most common reasons identified for failing to report issues were fear of retaliation and a belief that nothing would prevail from the reports. Method:Using Black's study as a model, reporting data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
28
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 12 publications
4
28
0
6
Order By: Relevance
“…Some studies show a threat from organizational silence to patient safety. Maxfield et al 52 and Cole et al 19 observed that alarmingly few medical practitioners confronted their colleagues when they became aware of a poor judgment that could cause harm. Lack of confidence, concerns about the effects of their involvement, and fear of retaliation are some reasons why healthcare providers are reluctant to speak, especially if the issue is administrative or organizational in nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies show a threat from organizational silence to patient safety. Maxfield et al 52 and Cole et al 19 observed that alarmingly few medical practitioners confronted their colleagues when they became aware of a poor judgment that could cause harm. Lack of confidence, concerns about the effects of their involvement, and fear of retaliation are some reasons why healthcare providers are reluctant to speak, especially if the issue is administrative or organizational in nature.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that this phenomenon is widespread among nurses, especially in relation to ethical issues 16,17 . Harmanci Seren et al 18 and Cole et al 19 noted how organizational silence could be detrimental to patient safety because of the preference of nurses to remain silent, primarily due to fear and isolation, and for administrative and regulatory reasons. If nurses feel the administration does not welcome their issues, they tend to solve problems themselves, compromising patient situations 7,20,21 …”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have identified the importance of open and respectful communication about addressing patient safety, potential missed care and other malpractice behaviours of staff to protect patients from harm (Martinez et al., 2015; Okuyama, Wagner, & Bijnen, 2014). However, despite the importance of speaking up and/or reporting, available evidence has shown that many health care professionals including nurses often hesitate to speak up, voice out their concerns and remain silent on issues that relate to patient care and nursing standards (Cole et al., 2019; Hall, Klein, Betts, & DeRanieri, 2018; Vrbnjak, Denieffe, O’Gorman, & Pajnkihar, 2016) citing a fear of retaliation as a common reason (Cole et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of reporting and/or speaking up about patient care issues and violation of nursing standards in the enhancement of patients' outcomes (Cole et al, 2019;Hall et al, 2018;Martinez et al, 2015;Okuyama et al, 2014;Vrbnjak et al, 2016), there is little in the literature assessing organisational silence among nurses. Besides, available studies about organisational silence in the nursing sector include small samples (<400), which could potentially affect the generalizability of the study findings, and tend to focus on underlying reasons that lead nurses to remain silent, rather than on individual nurse and hospital characteristics that explain this silence (Çaylak & Altuntas, 2017;Seren et al, 2018;Yalcin & Baykal, 2012;Yurdakul et al, 2016).…”
mentioning
confidence: 99%
“…Another notable finding of the present study is that none of the near misses identified were actually advised to the health centre's incident-report system, even though the information could be supplied anonymously. In our study, the causes underlying the absence of officially reporting have not been analysed; this issue should be studied carefully in primary care to identify these possible causes and thus improve the results obtained (Cole et al, 2019;Miller et al, 2017). Moreover, nurses should be instructed on the importance of reporting near miss events (Vrbnjak et al, 2016).…”
Section: Discussionmentioning
confidence: 94%